2009
DOI: 10.1007/s00024-009-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Gravity Variations near Shrinking Vatnajökull Ice Cap, Iceland

Abstract: Repeated gravity measurements were carried out from 1991 until 1999 at sites SE of Vatnajökull, Iceland, to estimate the mass flow and deformation accompanying the shrinking of the ice cap. Published GPS data show an uplift of about 13 ± 5 mm/a near the ice margin. A gravity decrease of -2 ± 1 lGal/a relative to the Höfn base station, was observed for the same sites. Control measurements at the Höfn station showed a gravity decrease of -2 ± 0.5 lGal/a relative to the station RVIK 5473 at Reykjavík (about 250 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…From GIA studies on Vatnajökull, researchers also found viscosity for upper mantle beneath Iceland lower than ~5 × 10 18 Pa s [ Sjöberg et al ., ; Fleming et al ., ; Jacoby et al ., ] that essentially indicates wet rheology [ Barnhoorn et al ., ]. However, the observed style of deformation in the Thingvellir graben fits well with the model prediction where strain rate is proportional to 3.5 order of the stress in a dry olivine rheology (Figure ) by satisfying other geophysical properties (see next section).…”
Section: Discussionmentioning
confidence: 99%
“…From GIA studies on Vatnajökull, researchers also found viscosity for upper mantle beneath Iceland lower than ~5 × 10 18 Pa s [ Sjöberg et al ., ; Fleming et al ., ; Jacoby et al ., ] that essentially indicates wet rheology [ Barnhoorn et al ., ]. However, the observed style of deformation in the Thingvellir graben fits well with the model prediction where strain rate is proportional to 3.5 order of the stress in a dry olivine rheology (Figure ) by satisfying other geophysical properties (see next section).…”
Section: Discussionmentioning
confidence: 99%
“…Jacoby et al . [] demonstrated the influence of lateral variations in the Earth's structure when comparing models to gravity data. However, they also showed that the results from these models do not provide a good fit to GPS data.…”
Section: Discussionmentioning
confidence: 99%
“…The GRACE data should be corrected for viscous deformation of the solid Earth due to glacial isostatic adjustment (GIA). Because of Iceland's unique tectonic setting, global models like Paulson et al (2007) (as adjusted by Geruo et al, 2013) are likely inappropriate (Fleming et al, 2007;Jacoby et al, 2009). The Vatnajoköll ice cap is highly sensitive to GIA (Ivins, 2014), and GIA modeling for Iceland is non-trivial.…”
Section: Methodsmentioning
confidence: 99%